(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aims to measure the extent of the impact of Earnings quality in the continuity of the company for a sample of private commercial banks listed on the Iraq Stock Exchange. The research sample included (15) of the listed commercial banks that continue to issue their financial statements for the period from (2009-2018).The research relied on three main models of measurement and on four steps. The first step is to measure the Persistence (Earnings Quality) by Depending the sustainability model. While the second step included measuring the Predictability of accounting profits by deriving the square root of the disparity of the estimation error from the first model Persistence (Earnings Quality), and the third step included measuring the prediction of financial failure and the continuity of the Banks, while the fourth step focused on measuring the extent of the impact of the Earnings Quality (Persistence) and (Predictability) as an independent variable over the main dependent variable represented by the continuity of the Banks and the prediction of financial failure using Simple linear regression analysis method., the most important of which are: • The majority of Iraqi banks listed on the Iraq Stock Exchange in general are characterized by (Earnings Quality), in addition to that they are distinguished by non- floundering or financial failure as shown by the results of the study. • There is a significant statistically significant impact between the Persistence (Earnings Quality) and the continuity of the company, as well as the existence of a significant statistically significant impact between the (Predictability) of accounting earnings and the continuity of the Banks. The most important recommendations reached were: • We recommend that banks whose profits do not enjoy continuity need to find profitable investment opportunities with high economic feasibility in order to enhance the sustainability of their profits. • Not limiting the use of financial indicators extracted from the bank’s accounting data in order to measure continuity, as this must also extend to linking non-financial indicators that take into account the variables associated with the company’s internal and external environment.